Situational Willingness to Communicate in English: Voices from Indonesian Non-English Major University Students - Adaninggar Septi Subekti (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This study investigated the perspectives of Indonesian non-English major university students on factors that could affect their Willingness to Communicate (WTC) in English as a situational affective construct affected by various surrounding factors. Involving seven university student participants from three categories of WTC level (low, medium, and high) in individual semi-structured interviews, the study found seven emerging themes through Thematic Analysis. First, supportive peers were attributed to higher WTC and unsupportive peers to lower WTC. Second, learners, especially those with low WTC, reported higher WTC when they were among classmates they already know. Third, learners reported higher WTC when they perceived their teachers as caring, patient, and supportive, showing empathy of learners’ struggle. Fourth, learners who perceived themselves as having low self-perceived communication competence (SPCC) would likely have less WTC. Fifth and sixth, learners had higher WTC when they were to speak among few interlocutors and were given some time to prepare for their talking. These two were found especially among learners with low WTC. Seventh, learners with medium and high WTC was found to have pleasant and successful previous experiences in using English whilst those with low WTC reported upsetting experiences with the language. Based on the findings, pedagogical implications and suggestions for future studies were presented.